'The instinct of resistance to evil': Postmemory and the Ukrainian national imaginary in Oksana Zabuzhko's novel The Museum of Abandoned Secrets. (April 2022) - Kazanova, Yuliya
Building on Marianne Hirsch's concept of postmemory, this article examines Oksana Zabuzhko's latest novel The Museum of Abandoned Secrets as postmemorial fiction, which articulates the trauma of Soviet political repressions in the post–World War II period and in the 1970s via the perception of the second and third generation. The affiliative postmemory about World War II in Ukraine from the viewpoint of Ukrainian Insurgent Army partisans is emplotted via an original generic combination of contemporary Holocaust fiction and romances of the archive. Postmemory is used in the novel to shape a mythologised alternative historical narrative that reconceptualises the country's difficult past as a story of heroic resistance.